The Respon Produksi Terung Ungu (Solanum MELONGENA L.) Terhadap Pemberian Pupuk Kandang Sapi Npk 16-16-16: Agribusiness sector - Liris Gulo; Rahmaniah Harahap; Lutfi Henderlan Harahap (Jurnal Agriuma, 2023)
The goal of the researchers is to understand how Tanaman Tanaman Terung Ungu (Solanum melongena L.) responds to the purchase of pupuk kandang sapi and pupuk NPK 16-16-16. The current study makes use of the Rancangan Acak Kelompok (RAK) Faktorial, which has three ulangan and two factors. The first factor is Pupuk Kandang Sapi (K), which has three taraf: control, one kilogram per plot, and two kilograms per plot, and the second factor is Pupuk NPK (N), which has three taraf: control, fifty grams per plot, and one hundred grams per plot. Panjang buah cm, jumlah buah per plot, and berat buah per plot are the parameters that were modified. The findings of the study indicate that Pupuk Kandang Sapi's involvement significantly affected the production of tanaman terung ungu with regard to the parameters panjang buah cm, jumlah buah per